AWARENESS OF THE CORPORATE NEEDS AMONG MANAGEMENT STUDENTS: THE ROLE OF MBA FACULTY MEMBERS - Kumar Das, Dr. Santanu Kumar (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this empirical study is to identify the different pedagogies used by MBA faculty members to inculcate wisdom driven practices among student for job needs of corporate and to suggest different techniques which MBA faculty members can use for students to fulfill corporate needs. For this 5 skills have been identified by industry experts. On each skill, 5 pedagogies were identified by academicians. A questionnaire was formed on nominal scale and sent to 40 faculty members. The data was analyzed through one proportional Z test. The result of the study shows 65 % of management faculty members of good Management Colleges of Odisha conduct book review sessions in management class at least once in a month and assigns students to build at least one case study in a semester. This study will help MBA schools in India to better understand the corporate need from MBA students and techniques which can be used by them to fulfill corporate need. This study is limited to identify the pedagogies used by MBA faculty members to make students understand the corporate need of someGood Management colleges. This study can be further taken over as comparison between Indian MBA colleges and other countries MBA colleges.